A Closer Look at ACE2 Signaling Pathway and Processing during COVID-19 Infection: Identifying Possible Targets - Pia V. Sodhi; Francoise Sidime; David D. Tarazona; Faviola Valdivia; Kelly S. Levano (Vaccines, 2022)
Since the identification of its role as the functional receptor for SARS-CoV in 2003 and for SARS-CoV-2 in 2020, ACE2 has been studied in depth to understand COVID-19 susceptibility and severity. ACE2 is a widely expressed protein, and it plays a major regulatory role in the renin–angiotensin–aldosterone System (RAAS). The key to understanding susceptibility and severity may be found in ACE2 variants. Some variants have been shown to affect binding affinity with SARS-CoV-2. In this review, we discuss the role of ACE2 in COVID-19 infection, highlighting the importance of ACE2 isoforms (soluble and membrane-bound) and explore how ACE2 variants may influence an individual’s susceptibility to SARS-CoV-2 infection and disease outcome.